Schools and multicultural Society - Ilun Lailatul Habibah; Helmi Muhammad (LPPM Sekolah Tinggi Ilmu Ushuluddin Darussalam Bangkalan Madura, 2021)
On the basis of a library research study of various library items related to communities and schools that are clashed with multicultural terminology, this paper has been prepared. According to the approach, the data collecting techniques utilised in this study are documented procedures, in which data is gathered through documents referred to as library materials. Content analysis is used to analyse the data gathered in this study. It emerged that multicultural schools and communities are institutions of higher education that recognise the existence of a wide range of distinct identities in the community and are prepared to accept all of them